Performance analysis of modified dynamic voltage restorer (DVR) employed to a grid connected solar PV system - Pal, Rakeshwri; Gupta, Sushma (International Journal of Engineering and Technology, 2018)
Among various power quality problems, voltage sag and swell are dominant where loads are very sensitive to the voltage disturbances. Various custom power devices are introduced recently to overcome these voltage issues, dynamic voltage restorer (DVR) is one of them. It offers very cost effective solution for problems such as voltage sag, swell and harmonics by establishing the proper voltage level during voltage disturbances to protect sensitive loads. In this paper, performance of DVR to improve power quality is done for solar photovoltaic (PV) based generation system feeding the grid and the three phase linear load. Solar PV generation system is implemented with an incre-mental conductance (IC) maximum power point tracking (MPPT) technique.Â The DVR is connected in between solar PV system and load. The basic structure of DVR is modified by using the photovoltaic system as an alternative to DC source and in place of conventional 2-level voltage source converter (VSC) neutral point clamped (NPC) multi level inverter is used. The system performance is analyzed in the MATLAB/Simulink environment. The simulation results justified the efficiency of modified DVR in the mitigation of voltage sag in distri-bution system. Improvement of power quality by stabilizing voltage during fault and promoting renewable energy is the main framework of this work.Â Â